Undetected Takayasu arteritis presenting as severe hypertension in children: a report of two cases - Wirawan, Muhammad Taufik; Murni, Indah Kartika; Patria, Suryono Yudha; Arafuri, Nadya; Noormanto, Noormanto; Nugroho, Sasmito (Indonesian Pediatric Society, 2024)
Takayasu arteritis (TA) is a rare chronic granulomatous vasculitis mainly affecting the aorta and its main branches. Clinical presentations of TA are non-specific, especially in the initial phase, which likely contributes to delayed diagnosis besides the rarity of the disorder. Childhood-onset of TA is associated with significant morbidity and mortality. This case report aimed to present two rare cases of acute symptomatic severe hypertension in children due to TA.